Determination of the average absorbed energy of electrons beam in objects at radiation processing - Lazurik, V.T.; Lazurik, V.M.; Popov, G.Ph.; Zimek, Z. (Вопросы атомной науки и техники, 2019)
A new conservative computational procedure is proposed for calculating the average absorbed energy of electron radiation in objects undergoing radiation processing. Semi-empirical relationships were obtained and software for dosimetry of electron radiation was developed. A comparison was made of the results obtained using the proposed method with the results of known and traditional methods of electron radiation dosimetry as well as with the results of measurements performed at the sterilization center of the Institute of Nuclear Chemistry and Technology, Warsaw, Poland was carried out. Запропоновано нову консервативну обчислювальну процедуру розрахунку середньої поглиненої енергії випромінювання електронів в об'єктах, які проходять радіаційну обробку. Отримано напівемпіричні співвідношення і створено програмне забезпечення для дозиметрії електронного випромінювання. Проведено порівняння результатів, отриманих з використанням запропонованого методу, з результатами відомих і традиційних методів дозиметрії електронного випромінювання, а також з результатами вимірювань, виконаних у стерилізаційному центрі Інституту ядерної хімії і технологій, Варшава, Польща. Предложена новая консервативная вычислительная процедура расчета средней поглощенной энергии излучения электронов в объектах, проходящих радиационную обработку. Получены полуэмпирические соотношения и создано программное обеспечение для дозиметрии электронного облучения. Проведены сравнения результатов, полученных с использованием предложенного метода, с результатами известных и традиционных методов дозиметрии электронного излучения, а также с результатами измерений, выполненных в стерилизационном центре Института ядерной химии и технологий, Варшава, Польша.